189k views
5 votes
Please help fassssst

Please help fassssst-example-1

1 Answer

5 votes

Answer:


(9)/(2)

Explanation:

You can do this using the quadratic equation:


x =\frac{-b\pm\sqrt{b^(2)-4ac}}{2a}

Let's first setup our expression:

4x² + 12x = 135

the quadratic formula is:

ax² + bx + c = 0

4x² + 12x - 135 = 0

Then:

a = 4

b = 12

c = -135

Now we plug in our coefficients and solve:


x =\frac{-12\pm\sqrt{12^(2)-4(4)(-135)}}{2(4)}

We solve for both to determine the positive one:


x =\frac{-12+ \sqrt{12^(2)-4(4)(-135)}}{2(4)}
x =\frac{-12- \sqrt{12^(2)-4(4)(-135)}}{2(4)}


x =(-12+ √(144+2160))/(8)
x =(-12- √(144+2160))/(8)


x =(-12+ √(2304))/(8)
x =(-12- √(2304))/(8)


x =(-12+ 48)/(8)
x =(-12- 48)/(8)


x =(36)/(8) = (9)/(2)
x =(-60)/(8) = (-15)/(2)

So if you are looking for a positive solution, just take the positive one as x.

User Terry G Lorber
by
5.7k points